Cuidados de enfermería y su relación en la prevención de enfermedades respiratorias agudas en trabajadores de la Bananera Zaragoza. Babahoyo. Los Ríos. octubre 2018-abril 2019 - Peralta Moran, Wendy Melissa (2019)
Introduction. - This research project investigates acute respiratory diseases (ARD), are diseases of the respiratory tract, caused mostly by viruses, bacteria and others. Nursing care in affecting the health of banana workers related to land and aerial handling and spraying, and affecting the health of a population surrounded by banana plantations Objectives. - To determine the relationship between nursing care and the prevention of acute respiratory diseases in banana workers in Zaragoza. Babahoyo, Los Ríos, October 2018-April 2019 Methodology. - Descriptive - explanatory study, with Inductive-deductive methods, the sample consisted of 66 workers and workers of the Zaragoza banana plantation, direct observation techniques and surveys were applied through a questionnaire of pre-prepared questions Results. - They gave very important aspects for the taking of alternatives to the nursing staff, there was predominance of the age group of 31 to 40 years of age with 50%, of the male sex with 83%, The prevention of the risk factors as an allocation of complete team among the workers is partial, also stressing that the company has not given nursing care in the management of respiratory diseases. Conclusions. - The workers manifest the need for the presence of nursing staff to receive an educational plan in the prevention and management of respiratory diseases, and individual home prevention